ANALISIS HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN IKAN NILA DI DESA KOTO TINGGI - Rika Santi; Heffi Christya Rahayu; Ratna Dewi (Jurnal Ekonomi Bisnis Kompetif, 2026)
This research aims to analyze the impact of price and product quality on tilapia purchasing decisions in Koto Tinggi Village. The phenomenon found in the field shows that although tilapia is one of the fishery commodities that is in high demand by the public, tilapia purchasing decisions show a complex interaction between price, product quality and purchasing decisions. The research method used in this research is a quantitative approach with multiple linear regression analysis techniques assisted by SPSS version 21 software. The population in this research is all tilapia buyers in Koto Tinggi Village. The sample determination is carried out using the Accidental sampling technique, while the number of samples is calculated using the Hair et al formula, resulting in 110 research subjects. Data collection is carried out through observation, interviews, and distribution of questionnaires to tilapia buyers in Koto Tinggi Village who are used as research subjects. The collected data is then analyzed to determine the impact of each independent variable on the dependent variable. The results of the research show that price has a positive and significant impact on tilapia purchasing decisions in Koto Tinggi Village. Furthermore, product quality has also been shown to have a positive and significant impact on tilapia purchasing decisions in Koto Tinggi Village. Simultaneously, price and product quality have a positive and significant impact on tilapia purchasing decisions in Koto Tinggi Village.